"Code-alternation of Yoruba-English bilinguals and their acceptability " (2016)
"The phenomenon of code alternation (C A) as a powerful language strategy existing in all communities in the world is very common place among Nigerian bilinguals. However, this common-placism does not translate into acceptability among the participants. As should be expected, different groups of people in the society are reflected in the patterns and use of CA, suggesting that social forces affect the performance of CA, making distinctions from those basic factors controlling basic structure with which they interact. It is also common knowledge that when speakers are bilinguals and CA is a component of the community, the type of code choices they make becomes a label for them, arising from adverse effect of the phenomenon regarded as a demerit. Accordingly, this paper sets out to provide quantitative evidence on the acceptability of these choices using selected Yoruba- English bilinguals. The findings reveal that there are variations in attitude to CA, the dominant one being positive. The implications of this for language instructions have been discussed. "